1988
DOI: 10.1084/jem.167.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Giardia lamblia. Detection of N-acetyl-D-glucosamine as the only surface saccharide moiety and identification of two distinct subsets of trophozoites by lectin binding.

Abstract: Lectins and glycosidases of known sugar specificity were used as probes to analyze the surface carbohydrate moieties of G. lamblia trophozoites and in particular to determine whether chitin or oligomeric D-GlcNAc is present in the trophozoite form of the parasite as well as on the cyst. Of 13 lectins with varying sugar specificity, only D-GlcNAc-specific lectins bound specifically to the trophozoite surface as determined by light microscopy and EM. A striking finding was the identification of two distinct subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…6). This high degree of conservation is consistent with an ancestral and continuing role of chitin in cell walls of many eukaryotes (4,7,43,44,55,57).…”
Section: Prevalence Of Cell Wall-related Sequences In Fungisupporting
confidence: 51%
See 1 more Smart Citation
“…6). This high degree of conservation is consistent with an ancestral and continuing role of chitin in cell walls of many eukaryotes (4,7,43,44,55,57).…”
Section: Prevalence Of Cell Wall-related Sequences In Fungisupporting
confidence: 51%
“…Cavalier-Smith has argued that fungal cell walls are derived from ancestral chitinous walls of desiccation-resistant cysts in many protist clades (7,8). Certainly, chitinous cysts and spores are present in other eukaryote kingdoms, including Amoebozoa (such as Entamoeba [11]), Chromalveolata (Phytophthora [43,44]), and Excavata (Giardia [57]). In addition, S. cerevisiae walls share extracellular disulfide cross-links and GPI-anchored cell adhesion molecules with Amoebozoa, perhaps the earliest-diverged eukaryotes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, at the concentration of WGA used in this study, i.e., 100 ttg/ml we found that only 10.6% of trophozoites were agglutinated by the lectin (data not shown) even though it binds to trophozoite glycoproteins as assayed by fluorescence microscopy (9), light and electron microscopy (10), and FACSO analysis (11). The basis for this lack of cell agglutination despite the presence of numerous WGA-binding sites on the trophozoite surface glycoconjugates is not clear.…”
Section: Resultsmentioning
confidence: 83%
“…Organisms were harvested, washed three times in PBS, and lysed with 1% Triton X-100 in PBS containing 2 mM PMSF overnight at 4°C. Lysates were centrifuged at 175 g for 5 min to pellet nuclei and the supematant boiled with sample buffer before electrophoresis on a 7% SDS-polyacrylamide gel (10). Separated proteins were electrotransferred to nitrocellulose and probed with 1 ,ug/ml of biotinylated WGA, using the avidin-biotin alkaline phosphatase technique as described earlier (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation